Transformasi Ekonomi Berkelanjutan di Indonesia melalui Produk Green Sukuk Perspektif Maqāṣid al-Syarī‘ah - Ittasyaq, Nurul Laili; Sholihin, M.; Prawoto (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
The environmental crisis in Indonesia is marked by various problems that threaten human life and various economic sectors. The Indonesian government has issued green sukuk products as an effort to improve the environment and provide alternative investments for the public. This study examines the potential of green sukuk products in promoting sustainable economic development in Indonesia from the perspective of maqāṣid al-syarī‘ah. This study uses a qualitative approach with data derived from literature related to sukuk, green sukuk regulations in Indonesia, and the maqāṣid al-syarī‘ah framework. This study will emphasize the thoughts of Imam al-Syatibi in his monumental work al muwafaqot in which he argues about the concept of istiqro'i in the application of the maqāṣid al-syarī‘ah paradigm to arrive at the qosd sharia objectives. Sheikh Thohir Ibn Asur's thoughts on maqāṣid al-syarī‘ah are also used as a basis for analyzing this research. The results of the study indicate that green sukuk has great potential to become a key pillar in the transformation of a sustainable economy in Indonesia. The integration of maqāṣid al-syarī‘ah in the implementation of green sukuk can ensure that economic growth is not only oriented toward financial gain but also toward achieving syariah objectives that prioritize environmental sustainability and social justice.